1997
DOI: 10.1177/0265407597141005
|View full text |Cite
|
Sign up to set email alerts
|

Relating Aggressive and Victimization Behaviors to Children's Sociometric Status and Friendships

Abstract: The present study examined peer nominations of pupils in Grades 3-6 (9-12-year-olds) for aggressive and victimization behaviors in relation to peer group sociometric status (popular, average, rejected) and number of mutual friends (reciprocal nominations). Rejected children, relative to other children, were perceived as higher both in aggression and in being victimized (both physically and verbally) and had the smallest number of mutual friends. In addition, the mutual friends of rejected status boys were perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
2
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 17 publications
10
33
2
5
Order By: Relevance
“…Furthermore, the finding that preschool bullies tend to affiliate with other bullies corresponds with studies among school-age children, which showed that behaviorally similar children cluster together (Haselager et al 1998;Pellegrini et al 1999). This affiliation of aggressive children might lead to an increase in bullying behavior as they adapt their behavior to each other (Dishion et al 1994) which is in agreement with studies among school-age children (Boulton and Underwood 1992;Olweus 1978;Ray et al 1997;Rigby 1996).…”
Section: Preschool Bulliessupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, the finding that preschool bullies tend to affiliate with other bullies corresponds with studies among school-age children, which showed that behaviorally similar children cluster together (Haselager et al 1998;Pellegrini et al 1999). This affiliation of aggressive children might lead to an increase in bullying behavior as they adapt their behavior to each other (Dishion et al 1994) which is in agreement with studies among school-age children (Boulton and Underwood 1992;Olweus 1978;Ray et al 1997;Rigby 1996).…”
Section: Preschool Bulliessupporting
confidence: 86%
“…In accordance with research conducted in primary education, there is empirical evidence in early education years indicating that victims and bully-victims had fewer reciprocal relationships than non-involved children (Boulton and Underwood 1992;Ray et al 1997;Rigby 1996). Having no friends in the preschool context may thus be considered a social risk factor for being victimized.…”
Section: Preschool Victimssupporting
confidence: 65%
“…Extending these previous studies on the protective function of friends, the current study showed that friendship can also exacerbate victimization. Victimized youth were hypothesized to have a hard time finding friends to begin with, as they are often rejected by their peers and unattractive as friends as they may pose a threat to their friend's social standing in the group (Boulton, in press;Hodges et al, 1997;Ray et al, 1997). Indeed, the current study showed that adolescents high in relational victimization were unlikely to be selected as friends and, moreover, the friends they had increased in victimization themselves.…”
Section: Discussionmentioning
confidence: 75%
“…Befriending victimized youth can be regarded as risky in the eyes of non-victimized peers, because it may pose a risk to become victimized as well. Indeed, friends of victimized youth are likely to be rejected in the peer group (Ray, Cohen, Secrist, & Duncan, 1997). It can thus be argued that peers avoid befriending victimized youth to prevent becoming rejected or even victimized themselves (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Good peer relations are essential for many reasons. Sociometric unpopularity is usually associated with a number of deficits (Bierman, Smoot, & Aumiller, 1993;Hymel et al, 2002;Ray, Cohen, Secrist, & Duncan, 1997;Volling, MacKinnon-Lewis, Rabiner, & Baradaran, 1993). Moreover, early peer difficulties are predictive of later maladjustment.…”
Section: Discussionmentioning
confidence: 99%